2021
DOI: 10.1029/2020wr028700
|View full text |Cite
|
Sign up to set email alerts
|

Grain‐Size Distribution and Propagation Effects on Seismic Signals Generated by Bedload Transport

Abstract: Rivers are key features of ecosystems, transferring water, dissolved, and particulate matter across the Earth's surface. Driven by the power of moving water, sediment helps rivers to shape landscapes and contribute to the evolution of river morphology (Leopold et al., 1964). Sediment in rivers is either carried as suspended load or as bedload (rolling, sliding, or saltating on the bed). Bedload contributes to channel changes, such as creating micro-and macroforms, narrowing, widening, shifting, aggrading, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 56 publications
(150 reference statements)
1
17
0
Order By: Relevance
“…Models concerning bedload transport predict that sediment flux and transported grain sizes are major control parameters, mainly setting the rate and the amplitude of particle impacts against bed roughness elements. These theoretical expectations have been verified through experiments and field observations under relatively low bedload transport rates (Bakker et al., 2020; Gimbert et al., 2019; Lagarde et al., 2021).…”
Section: Introductionmentioning
confidence: 78%
“…Models concerning bedload transport predict that sediment flux and transported grain sizes are major control parameters, mainly setting the rate and the amplitude of particle impacts against bed roughness elements. These theoretical expectations have been verified through experiments and field observations under relatively low bedload transport rates (Bakker et al., 2020; Gimbert et al., 2019; Lagarde et al., 2021).…”
Section: Introductionmentioning
confidence: 78%
“…A number of recent studies have shown the relatively good performance of the FMI model to retrieve bedload transport estimates (Dietze et al, 2019(Dietze et al, , 2022aLagarde et al, 2021). Yet, multiple sources of uncertainty were shown to possibly affect the performance of the bedload transport inversion.…”
Section: Model Applicationmentioning
confidence: 99%
“…The FMI uses a least-squared procedure to fit the measured empirical seismic spectrum to synthetic ones produced by the paired models for random combinations of water depth 𝐴𝐴 𝐴 and unit bedload transport rate 𝐴𝐴 𝐴𝐴b estimated within their own plausible range, to invert the most likely values of 𝐴𝐴 𝐴 and 𝐴𝐴 𝐴𝐴b at each targeted time-step (Dietze et al, 2019). Bedload transport and water depths were inverted from the paired FMI, requiring constraints on nine parameters, which can be separated into three classes following Lagarde et al (2021); (a) the river morphology parameters, which include the channel gradient 𝐴𝐴 𝐴𝐴 (radians), the channel width 𝐴𝐴 𝐴𝐴 (m), and the distance between the channel centerline and the seismic sensor 𝐴𝐴 𝐴𝐴0 (m); (b) the grain-size distribution (GSD) parameters, which include the median grain-size 𝐴𝐴 𝐴𝐴50 (m) and the standard deviation 𝐴𝐴 𝐴𝐴𝑔𝑔 (-) of a parametric log-raised cosine function fitted to discrete measured particle classes (Tsai et al, 2012); and (c) the seismic ground properties, which are described by Green's function as (Bakker et al, 2020;Tsai et al, 2012):…”
Section: Seismic Model Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, both turbulent flow and sediment transport during floods generate ground motion in different frequency bands (Schmandt et al, 2013;Gimbert et al, 2014) that can be used to track the flood dynamics (e.g., Cook et al, 2018). Surface seismic waves are generated by impact forces exerted by mobile particles on the river bed (e.g., Tsai et al, 2012;Gimbert et al, 2019) and ambient seismic measurements have recently been used to monitor fluxes associated with transported bed material Bakker et al (2020); Lagarde et al (2021). In the past decade, near-river seismic monitoring has been conducted during moderate-magnitude floods (e.g., Burtin et al, 2016;Roth et al, 2016) and controlled small-magnitude flow events (Schmandt et al, 2013(Schmandt et al, , 2017.…”
mentioning
confidence: 99%